Transport of Energetic Electrons in Solids Computer Simulation with Applications to Materials Analysis and Characterization - Dapor, Maurizio (Springer Tracts in Modern Physics, 2014)
This book presents the potential of the Monte Carlo (MC) technique to solve mathematical and physical problems of great complexity. This book focusses on the study of the electron-solid interaction (transport MC) and presents some physical problems related to the transport of hot electrons in solid targets using transport MC. The numerical and theoretical results are validated through a comparison with experimental results. The author also addresses methodological aspects. In particular, systematic comparisons among different calculation schemes are presented. Different expressions for the calculation of cross sections and/or stopping power and different simulation methods are described and discussed.